The Effect of School Starting Age on Special Needs Incidence and Child Development into Adolescence - Simone Balestra; Beatrix Eugster; Helge Liebert (Center for Economic Studies and ifo Institute (CESifo), 2017)
Children starting school at older ages consistently exhibit better educational outcomes. In this paper, we underscore child development as a mechanism driving this effect. We study the causal effect of school starting age on a child's probability of developing special educational needs in early grades. We find that starting school at a relatively older age decreases the probability of developing special needs by approximately 6 percentage points. This decrease is due to a lower incidence of various behavioral and learning impairments. Importantly, the effect is not driven by non-expert over-referrals of relatively younger children to special needs services. The effect is persistent throughout compulsory schooling, resulting in higher test scores in grade eight. Although these performance differentials are significant, they do not affect labor market entry.
Keywords: I14; I21; J13; 330; school starting age; special needs; child development